ANALYZING THE EFFECTIVENESS OF IMPORT GOODS RELEASE FROM CUSTOMS AREAS IN THE INDONESIAN LOGISTICS SECTOR - Intan Ayu Lestari; Mashudi Mashudi (Antis Publisher, 2026)
Objective: This research is based on recurring issues in the process of releasing imported goods from bonded zones, as well as discrepancies between the quality (grade) of goods delivered and those ordered by importers. These issues significantly impact the effectiveness and efficiency of the import logistics supply chain. The objective of this study is to analyze the effectiveness of the handling process for the release of imported goods from bonded zones by PT. Mitra Kargo Indonesia. Method: This research employs a descriptive qualitative method, with data collected through interviews, observations, and documentation. Informants were selected using purposive sampling and consist of four employees of the company and one importer who collaborates with the company. The data analysis technique follows several stages: data collection, data reduction, data presentation, and drawing conclusions. Results: The release of imported goods can be effective when each stage, such as document submission, PIB preparation, customs clearance, delivery order processing, and release from the bonded zone, is carried out according to standard procedures with complete documentation. However, challenges arise from both internal and external factors, including data entry errors, document issues, procedural delays, port congestion, and inspection holds. Novelty: To ensure a smoother process, better coordination, accuracy, and system preparedness are essential.